PENGARUH PEMBERIAN TINGKAT KONSENTRASI LARUTAN FERMENTASI URIN SAPI DAN LAMA PERENDAMAN TERHADAP PERKECAMBAHAN BENIH TREMBESI (Samanea saman) - Intan Sri Mulyani; Andi Apriany Fatmawaty; Sri Ritawati (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
The research was aimed to know the effect of giving various concentrations level of cow urine fermentation solution and soaking time to seed germination of trembesi (Samanea saman). Research was conducted from April to June 2017 at Greenhouse Agroecotechnology Laboratory Faculty of Agriculture University of Sultan Ageng Tirtayasa. The research used a Randomized Complete Design and arranged in factorial, consisted of two factors. The first factor was cow urine concentration consisted of four factors: 0%, 25%, 50%, 75%. The second factor was the duration of immersion consisting of three factors namely: 6 hours,12 hours, and 18 hours. The results showed that cow urine fermentation concentration 75% gave best result to germination age parameter 1,77%/day, maximum growth potential 36,11%, germination 31,11%, growth rate 1,20%, normal sprout potency 33,8% and abnormal germination potential 2,22%. The duration of soaking of (6 hours) trembesi seeds gave the best results on the germination age parameter 3,41%/day, maximum growth potential 31,66%, germination 25,41%, growth rate 1,05 %, Potency of normal sprout 30,41%. There was no interaction between the various concentration levels of cow urine fermentation solution and the soaking time to seed to the observed parameters except on the observed age germination parameters at 0% cow urine treatment with soaking time to seed 6 hours, and 75% cow urine treatment with soaking time to seed 6 hours (1,33% / day). Keywords: Soaking time to seed, Trembesi (Samanea saman), Urine concentration